2003
DOI: 10.2337/diabetes.52.2.291
|View full text |Cite
|
Sign up to set email alerts
|

PPAR-γ Activation Mediates Adipose Depot−Specific Effects on Gene Expression and Lipoprotein Lipase Activity

Abstract: This study sought to determine whether the adipose depot؊specific (subcutaneous [SF] vs. visceral [VF])action of peroxisome proliferator؊activated receptor-␥ (PPAR-␥) agonists on fat deposition extends to the expression of lipoprotein lipase (LPL) and other key adipose lipid metabolism genes, and whether changes in LPL impact triglyceridemia. Rats were fed a standard diet or an obesity-promoting diet for 3 weeks, with or without treatment with COOH, a nonthiazolidinedione PPAR-␥ agonist. Treatment effects were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
104
2
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(126 citation statements)
references
References 54 publications
18
104
2
2
Order By: Relevance
“…The study confirmed the well-established actions of rosiglitazone on morphometric variables, indices of insulin sensitivity and lipidaemia [18][19][20][21]. Several lines of evidence suggest that thiazolidinediones exert their beneficial effects on whole-body insulin sensitivity partly by reducing circulating NEFAs and the consequent exposure of nonadipose tissues to the deleterious effects of NEFA metabolites on insulin signal transduction [2].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The study confirmed the well-established actions of rosiglitazone on morphometric variables, indices of insulin sensitivity and lipidaemia [18][19][20][21]. Several lines of evidence suggest that thiazolidinediones exert their beneficial effects on whole-body insulin sensitivity partly by reducing circulating NEFAs and the consequent exposure of nonadipose tissues to the deleterious effects of NEFA metabolites on insulin signal transduction [2].…”
Section: Discussionsupporting
confidence: 78%
“…In vitro basal, NA-stimulated, and insulin-inhibited lipolysis Adipose explants (20)(21)(22)(23)(24)(25) In vitro exposure of explants to rosiglitazone Minced pieces (40 mg/well) of each of the four depots described above, obtained from four control, untreated, fasted rats, were incubated in 1 ml of DMEM (Invitrogen, Burlington, ON, Canada) supplemented with pure rosiglitazone (Cayman Chemical Company, Ann Arbor, MI, USA) to a final concentration of 10 μmol/l, or carrier DMSO for 12 h. Treatments were performed in duplicate for each rat. Fat explants were then removed and frozen in liquid nitrogen until RNA isolation and analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The orexigenic effect of PPARg agonism confirms earlier rodent studies. 9,25,26 Therefore, PPARg agonism prevents the anorectic effect of hypercorticosteronemia, but not its catabolic action on lean mass. These data further establish the important notion that the combined metabolic effects of HiCORT and PPARg agonism discussed below were independent from altered energy intake, a major potential confounder.…”
Section: Discussionmentioning
confidence: 99%
“…3 In addition to positive alterations in the adipokine profile that include increased expression of the insulin-sensitizing adiponectin, 4,5 the beneficial effects of PPARg agonists on insulin sensitivity and on the lipid profile appear to be partly attributable to lipid retention in adipose tissue and consequent reduction in lipid exposure of nonadipose tissues. [6][7][8] The lipid retention action of PPARg agonism is linked to its ability to induce the expression of genes involved in lipid accumulation, including lipoprotein lipase (LPL), 9 acyl-CoA synthase 1 (ACS1), 10 diacylglycerol acyltransferase 1 (DGAT1), 11 fatty acid synthase (FAS), 12 and cytosolic phosphoenolpyruvate carboxykinase (PEPCK-C). 13 PPARg agonism also affects local glucocorticoid (GC) metabolism in adipose tissue.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation